Research on Cleft Lip and Palate: What Is New? - Eloá Cristina Passucci Ambrosio; Paula Karine Jorge; Cleide Felício Carvalho Carrara; Maria Aparecida Andrade Moreira Machado; Thais Marchini Oliveira (MDPI AG, 2023)
Craniofacial development begins during the fourth week of intrauterine life (IUL) [...]